Juvenile myasthenia gravis in Norway: HLA-DRB1*04:04 is positively associated with prepubertal onset. - T H Popperud; M K Viken; E Kerty; B A Lie (PLoS ONE, 2017)
Juvenile myasthenia gravis (MG) is a rare autoantibody mediated autoimmune disorder targeting the neuromuscular endplate. The clinical hallmark is muscle weakness and fatigability. Disease aetiology is complex, including both genetic and environmental factors. The involvement of genes in the human leukocyte antigen (HLA) is well established in adult MG. However, HLA associations in European juvenile MG have not been studied. This case-control study aimed to investigate and characterize genetic risk factors in prepubertal and postpubertal onset juvenile MG.A population based Norwegian cohort of 43 juvenile MG patients (17 with prepubertal onset, 26 with postpubertal onset) and 368 controls were included. Next generation sequencing of five HLA loci (HLA-A, -B, -C, -DRB1 and -DQB1) was performed, and a positive association was seen with HLA-B*08 (OR (95% CI) = 3.27 (2.00-5.36), Pc = 0.00003) and HLA-DRB1*04:04 (OR (95% CI) = 2.65 (1.57-4.24), Pc = 0.03). Stratified in postpubertal and prepubertal onset, HLA-DRB1*04:04 was only positively associated with the latter (P = 0.01). The HLA-B*08 allele (12.9% in the controls), previously described associated with early onset adult MG, was most frequently observed in postpubertal onset MG (40.4%, P = 0.0002) but also increased among prepubertal onset MG (23.5%, P = 0.05).This study provides novel information about HLA susceptibility alleles in Norwegian juvenile MG where HLA-DRB1*04:04 was associated with prepubertal onset.